Kinerja Keuangan Pemerintahan Kabupaten/Kota Sebelum dan Sesudah Pengalokasian Dana Perimbangan - Slamet Widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
An assessment of the local government's financial performance can be used as input in the process of policy improvements in the future. Two decades of regional autonomy are considered as momentum to review some financial indicator performance of local governments to minimize their strong funding dependency on the central government. This study measures 258 cities/municipalities' government financial ratios namely the ratio of independence, the ratio of revenues effectiveness, the ratio of expenditure efficiency, the ratio of operational expenditure, the ratio of capital expenditure, and the ratio of revenues growth before and after receiving balancing transfer funds using secondary data (Local Government State Budget) from Ministry of Finance in 1995 and 2020. The analysis method used is One-way Anova. The purpose of the study was to see whether there are some differences in the ratio before and after receiving balance transfer funds from the central government. The results showed a significant difference between all ratios, with decreasing criteria in some financial ratios.